Between caravan and sultan : the Bayruk of southern Morocco, a study in history and identity - Mohamed, Mohamed Hassan, 1959- (Studies in the History and Society of the Maghrib, 2012)
This work presents a study of the history and identity of the Moroccan Bayruk family. The first part of the book gives an outline of the main referents in both the Bayruk vision of 'self', and academic discourses on Maghribian history: the dynasty, caravan and 'tribe'. It identifies discrepancies in scholarly presentations of the Bayruk and traces them back to two overlapping issues of translation and conception. For the remainder of the book a variety of sources are used to highlight the role of textuality in the creation of the Bayruk image in academic discourse. As a result this book demonstrates how the Bayruk family can be used as a case-study to revise the existing interpretations of Maghribian history and modes of identification.